Molecular identification by multiplex polymerase chain reaction of Pasteurella multocida in cattle and buffaloes in Baghdad: Ihab G. M. AL-Shemmari and A. M. H. Al-Judi - AL-Shemmari, Ihab G. M. (The Iraqi Journal of Veterinary Medicine, 2014)
The aim of this study was to identify pasteurella multocida and their types by PCR in cattle’s and buffaloesi bagdad from March to August 2012 on 204 animals , including 102 cattle and 102 buffaloes at slaughter houses from Baghdad .Blood samples and nasal swaps were collected , before slaughtering and lung tissues of slaughtered animal , and from 54 clinically suspected cases of pasteurellosis , including 27 bovines ,and 27 buffaloes the samples taken included blood and nasal swabs . Pasteurellamultocida were isolated from 94 animals include 49 cattle 45 buffaloes. The typing of the isolates by multiplex PCR for genotyping Pasteuerllamultocida revealed 93 isolates of type B , 31 from cattle and 62 from buffaloes ,and 81 isolates of type A , 55 from cattle and 26 from buffaloes .